Zauber Presser / Anis Suhaila Razman, Mardhiah Mat Din … [et al.] - Razman, Anis Suhaila; Mat Din, Mardhiah; Tawfik Teow, Muhammad Aidil; Sabri, Nor Farahin (2019)
The consumption of fruits and vegetables give many benefits to the individuals. It is essential to the people from all age group, especially children who are still growing up and adults that have certain illnesses which require certain vitamins and minerals supplementation. However, there are challenges in getting compliance from the individuals to consume the recommended amount of fruits and vegetables intake per daily consumption. The challenges may come from the individuals themselves or from the environmental factors. Thus, by taking he current advancement of multimedia and technology into account, a multi-functional product, together with application is created to assist the general public in achieving the recommended amount of fruits and vegetables. Besides, the people also get to know more knowledge on what kind of fruits or vegetables that can help treating certain health-related conditions that the individual suffers.